Role of Peace Keeping Army in Prevailing Justice to Second World Nations - E.H.J. FoEh, John; Ali, Yusuf (Dinasti International Journal of Management Science, 2024)
Peacekeeping has been used as a significant tool for the past six decades in solving crises that are dangerous to peace and security at the international level. Over the years the missions regarding peacekeeping have not only grown in size but have also seen an increase in complexity. A lot of personnel including police, military, civilians, and others deployed in United Nations peacekeeping operations around the world have reached unprecedented levels since the commencement of the latest millennium. When the peacekeeping missions began, they were largely governed by the body of principles that was unwritten and were more affected by the events people went through while working for decades rather than any specific statute. The conservation of global safety and tranquility was the main objective behind the formation of the United Nations. The main tool to achieve this objective is the process of peacekeeping.